New Brunswick: Development of a Web-based orientation program and enhancing senior nurses' mentoring skills - Auffrey, Marise; Cormier-Daigle, Monique; Gagnon-Ouellette, Anne (Nursing Leadership, 2012)
This project to help new nurse recruits integrate into the hospital work environment had two components: the development of a new web-based orientation tool in French for new recruits and mentor training for more experienced nurses. The aim of the first component was to redesign delivery of the nursing orientation program by assessing individual needs of new recruits and developing "just in time" information sessions with online access and e-learning modules. The second component aimed to develop a voluntary mentorship training program for senior nurses that offered training on the role and responsibility of mentors. A total of 30 orientation modules were created as resources that could be adapted to the needs of each nursing unit and accessed online. Sixty nurse recruits used the programs. A mentor training program was developed, and 28 nurses were trained as mentors. The mentorship literature and guides, produced in French, will be a valuable resource for francophone nurses across Canada.

Life expectancy gap between the Francophone majority and Anglophone minority of a Canadian population - Auger, Nathalie; Harper, Sam; Barry, Amadou D.; Trempe, Normand; Daniel, Mark (European Journal of Epidemiology, 2012)
Language is an important determinant of health, but analyses of linguistic inequalities in mortality are scant, especially for Canadian linguistic groups with European roots. We evaluated the life expectancy gap between the Francophone majority and Anglophone minority of Québec, Canada, both over time and across major provincial areas. Arriaga’s method was used to estimate the age and cause of death groups contributing to changes in the life expectancy gap at birth between 1989–1993 and 2002–2006, and to evaluate patterns across major provincial areas (metropolitan Montréal, other metropolitan centres, and small cities/rural areas). Life expectancy at birth was greater for Anglophones, but the gap decreased over time by 1.3 years (52% decline) in men and 0.9 years (47% decline) in women, due to relatively sharper reductions in Francophone mortality from several causes, except lung cancer which countered reductions in women. The life expectancy gap in 2002–2006 was widest in other metropolitan centres (men 5.1 years, women 3.2 years), narrowest in small cities/rural areas (men 0.8 years, women 0.7 years), and tobacco-related causes were the main contributors. Only young Anglophones <40 years in small cities/rural areas had mortality higher than Francophones, resulting in a narrower gap in these areas. Differentials in life expectancy favouring Anglophones decreased over time, but varied across areas of Québec. Tobacco-related causes accounted for the majority of the current life expectancy gap.

Francophone and Anglophone perinatal health: Temporal and regional inequalities in a Canadian setting, 1981-2008 - Auger, Nathalie; Park, Alison L.; Harper, Sam (Francophone and Anglophone perinatal health: Temporal and regional inequalities in a Canadian setting, 2012)
Objectives We evaluated temporal and regional inequalities in adverse birth outcomes between Anglophones and Francophones of a Canadian province. Methods Odds ratios and rate differences in preterm birth (PTB, <37 gestational weeks) and small-for-gestational-age (SGA) birth were computed for Anglophones relative to Francophones for singleton live births in Québec from 1981 to 2008 (N = 2,292,237), adjusting for maternal characteristics. Trends over time and residential region were evaluated. Results Rates of PTB and SGA birth overall were lower for Anglophones relative to Francophones, but temporal and regional trends varied by outcome. Although PTB rates increased over time, inequalities between Francophones and Anglophones were relatively stable. In contrast, inequalities in SGA birth narrowed over time as Francophone rates declined more than Anglophones. Inequalities in SGA birth favored Anglophones overall, but the gap gradually reversed in Montréal (the largest metropolitan center) to currently favor Francophones. Conclusions PTB and SGA birth rates favored Anglophones over Francophones. The linguistic gap was generally stable over time for PTB, but narrowed or reversed for SGA birth. Language may be used to capture inequalities in perinatal health in countries where different linguistic groups predominate.

Les inégalités sociales de santé chez les communautés francophones en situation minoritaire (CFSM) au Canada [numéro thématique] - Benoit, Monique; Bouchard, Louise; Garceau, Marie-Luce (Reflets, 2012)

La santé des francophones de l'Ontario. Un portrait régional tiré des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)

The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS) - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Makvandi, Ewa; Sedigh, Golnaz (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, 2012)
fs-ref-orig: Bouchard, L., Batal, M., Imbeault, P., Gagnon-Arpin, I., Makvandi, E., & Sedigh, G. (2012). The health of Francophones in Ontario. A region-by-region portrait developed from the Canadian community health survey (CCHS). Réseau de recherche appliquée sur la santé des francophones de l'Ontario. fs-code-orig: Bouchard-2012d

L'offre active des services de santé en français en Ontario : une mesure d'équité - Bouchard, Louise; Beaulieu, Marielle; Desmeules, Martin (Reflets, 2012)
Cet article fait état d’une recherche sur l’offre active de services en français en Ontario. L’étude avait pour objectifs de recenser les définitions de l’offre active de services en français; d’identifier les pratiques d’offre active (facilitateurs ou obstacles); d’identifier les indicateurs de mesure de l’offre active et de proposer des recommandations permettant d’améliorer l’offre active de services en français. À cette fin, une revue documentaire, une enquête auprès de professionnels oeuvrant dans le domaine de la planification des services de santé en français ainsi qu’un atelier de cartographie conceptuelle ont été entrepris. Mots-clés : minorité linguistique, services de santé, offre active, Loi 8

Do chronically ill, elderly Francophone patients believe they are adequately served by Ontario’s health care system? Exploratory study of the effect of minority-language communities - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Canadian Family Physician, 2012)

Les Franco-Ontariens âgés souffrant de maladies chroniques se perçoivent-ils bien desservis ? Une étude exploratoire de l'impact de la situation linguistique minoritaire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Le médecin de famille canadien, 2012)

Rapport d'enquête d'évaluation des besoins et de services de santé des francophones du Sud-Est - Bouchard, Louise; Gagnon-Arpin, Isabelle; Makvandi, E.wa (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)
fs-ref-orig: Bouchard, L., Gagnon-Arpin, I. et Makvandi, E. (2012). Rapport d'enquête d'évaluation des besoins et de services de santé des francophones du Sud-Est. Réseau de recherche appliquée sur la santé des francophones de l’Ontario. fs-code-orig: Bouchard-2012e

Quel avenir pour les services sociaux et de santé des communautés anglophones du Québec ? - Carter, Jane (Déclin et enjeux des communautés de langue anglaise du Québec, 2012)
Chapitre 6

How healthy are Manitoba’s Francophones? A summary of report, Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Ottawa, Manitoba Center for Health Policy, 2012)
A summary of the report, Health and Healthcare Utilization of Francophones in Manitoba / La santé et l’utilisation des services de santé des francophones du Manitoba by Mariette Chartier, Greg Finlayson, Heather Prior, Kari-Lynne McGowan, Hui Chen, Janelle de Rocquigny, Randy Walld, Michael Gousseau Summary written by Michelle Houlden

Quel est l’état de santé des francophones du Manitoba ? Sommaire du rapport intitulé La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Greg; Prior, Heather; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, University of Manitoba, 2012)

Health and healthcare utilization of Francophones in Manitoba - Chartier, Mariette; Finlayson, Gregory. S.; Prior, Heather. J.; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, 2012)

La santé et l'utilisation des services de santé des francophones du Manitoba - Chartier, Mariette; Finlayson, Gregory. S.; Prior, Heather. J.; McGowan, Kari-Lynne; Chen, Hui; de Rocquigny, Janelle; Walld, Randy; Gousseau, Michael (University of Manitoba, Manitoba Center for Health Policy, 2012)

Portrait des minorités de langue officielle au Canada : les francophones de l’Île-du-Prince-Édouard - Chavez, Brigitte; Lepage, Jean-François; Bouchard-Coulombe, Camille (Statistique Canada, 2012)
Réalisé grâce au soutien financier du Secrétariat des langues officielles de Patrimoine canadien, de Ressources Humaines et Développement des Compétences Canada (RHDCC) ainsi que du ministère de la Justice Canada, ce portrait de la population de langue française de l’Île-du-Prince-Édouard est le dixième d’une série de portraits démolinguistiques des minorités de langue officielle au Canada rédigés par la Section des statistiques linguistiques de Statistique Canada. Cette étude brosse un portrait statistique général de la minorité de langue officielle de l’Île-du-Prince-Édouard en s’appuyant sur des données de recensements de la population ainsi que sur celles de l’Enquête sur la vitalité des minorités de langue officielle au Canada menée en 2006. Le but d’un tel portrait est de présenter un ensemble de caractéristiques, de comportements et de perceptions de la population de langue officielle minoritaire en mettant en évidence les possibilités d’analyse que recèlent les données. Le présent document ne se veut ni un simple assemblage de tableaux ni une étude approfondie de la dynamique démolinguistique de la population de langue française de l’Île-du-Prince-Édouard. Il présente une information diversifiée sur un ensemble de thèmes et de problématiques qui revêtent un intérêt pour les minorités de langue officielle et pour quiconque s’intéresse à la situation passée, actuelle et future des populations de langue officielle en situation minoritaire au Canada. La première section de ce portrait démolinguistique porte sur le choix des critères de définition de la population de langue française de l’Île-du-Prince-Édouard qui seront utilisés aux fins de ce document ainsi que sur une brève description des sources de données utilisées. La seconde section présente différentes informations qui rendent compte de l’évolution de la population de langue française ainsi que sur la répartition et la concentration de cette population sur le territoire de l’Île-du-Prince-Édouard. Cette information est accompagnée d’une carte géographique présentée en annexe et d’un tableau détaillé sur l’effectif, le poids relatif et la répartition de la population de langue française de l’Île. La troisième section de ce portrait porte sur les principaux facteurs qui influent sur l’évolution de la population de langue française dans cette province ou qui en résultent, soit la transmission de la langue maternelle et l’effet de l’exogamie, la structure par âge, la mobilité linguistique intragénérationnelle et la migration interprovinciale. De plus, on y présente de l’information sur l’usage du français dans la sphère publique et sur l’évolution de la capacité de soutenir une conversation selon le groupe de langue maternelle. La quatrième section porte sur quelques secteurs clés pour la vitalité des communautés de langue officielle en situation minoritaire tels qu’identifiés dans la Feuille de route pour la dualité linguistique canadienne 2008-2013 : agir pour l’avenir1, soit la santé, la justice, l’éducation et les médias, les arts et la culture. Nous y présentons également des statistiques sur la participation communautaire, les caractéristiques de l’emploi et du revenu ainsi que sur l’utilisation du français au travail. Finalement, la dernière section de ce portrait présente des statistiques sur l’appartenance identitaire des francophones et leurs perceptions à l’égard de la présence du français dans leur communauté, de l’offre de services en français de la part du gouvernement fédéral, du respect des droits linguistiques ainsi qu’à l’égard du fait que des gens travaillent au développement de la communauté francophone.

Portrait of Official-Language Minorities in Canada: Francophones in Prince Edward Island - Chavez, Brigitte; Lepage, Jean-François; Bouchard-Coulombe, Camille (Statistics Canada, 2012)
This demolinguistic portrait of the French-speaking population in Prince Edward Island was undertaken with the financial support of Canadian Heritage’s Official Languages Secretariat, Human Resources and Skills Development Canada (HRSDC) and Justice Canada. It is the tenth in a series of demolinguistic portraits of official-language minorities in Canada, prepared by Statistics Canada’s Language Statistics Section. This study paints a general statistical portrait of the official-language minority in Prince Edward Island based on data from the Census of Population and the Survey on the Vitality of Official-Language Minorities in Canada, conducted in 2006. The purpose of such a portrait is to present a set of characteristics, behaviours and perceptions of the minority official-language population, exploiting the analytical opportunities contained in the data. This document is intended to be neither a mere collection of tables nor an in-depth study of the demolinguistic dynamics of the English-speaking population in Prince Edward Island. It presents a range of themes and issues that will be of interest to official-language minorities and anyone concerned with the past, present and future situation of minority official-language populations in Canada. Section 1 of this demolinguistic portrait concerns the criteria chosen in this study to define Prince Edward Island’s French-speaking population. It also provides a brief description of the data sources used. Section 2 presents varied information on the evolution of the French-speaking population and its geographic distribution and concentration in Prince Edward Island. This includes an appended map and a detailed table on the size, relative weight and distribution of the Island’s French-speaking population. Section 3 concerns the main factors that affect or are affected by changes over time in this province’s French-speaking population: transmission of mother tongue and the effect of exogamy; age structure; intragenerational linguistic mobility; and interprovincial migration. It also discusses the use of French in the public sphere and how the ability to conduct a conversation in that language has evolved according to mother-tongue group. Section 4 looks at a few sectors essential to the vitality of minority official-language communities, as identified in the Roadmap for Canada’s Linguistic Duality 2008–2013: Acting for the Future,1 namely health, justice, education and the media, the arts and culture. It also provides statistics on community participation, employment and income characteristics, and the use of French at work. The last section of this portrait presents statistics on the identity of Francophones and their perceptions regarding the presence of French in their community, the provision of federal government services in French, the respect for linguistic rights, and the fact that people are working to develop the Francophone community.

Quel avenir pour le projet autonomiste des communautés francophones en situation minoritaire ? Réflexion sur les politiques publiques canadiennes en matière de langues officielles - Chouinard, Stéphanie (Minorités linguistiques et société, 2012)
Nous tentons de mettre au jour quelques possibilités d’application, en matière de politiques publiques, des revendications de reconnaissance politique des communautés francophones en situation minoritaire (CFSM) du Canada, que nous organisons selon deux optiques différentes, soit l’autonomie et l’intégration. Après quelques considérations d’ordre sociopolitique et juridique, nous plaiderons pour une asymétrie dans l’élaboration des politiques publiques relatives à ces communautés. Nous soulignerons aussi le poids des enjeux de pouvoir dans la relation entre l’État et les CFSM, notamment sur le plan de la gouvernance, dans l’élaboration de ces politiques. Mots-clés : autonomie, politiques publiques, communautés francophones en situation minoritaire, communautés de langue officielle au Canada, participation politique

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 2 – Inventaire des services de santé disponibles en français et identification des déficits de services - De Moissac, Danielle; Ba, Halimatou; Gagné, Maryanne; Éthier, Sophie (Conseil communauté en santé du Manitoba, 2012)
Au Manitoba, des services de santé en français sont disponibles à Winnipeg, et plus précisément à Saint-Boniface et à Saint-Vital, où habite une forte concentration de francophones. L’objectif de ce deuxième volet de recherche sur l’accès des personnes âgées aux services de santé en français est de dresser un inventaire représentatif des services de santé publics, privés à but lucratif, privés à but non lucratif ou communautaires disponibles en français dans ces deux quartiers, pour ensuite identifier les déficits de services. On définit ici la disponibilité comme étant un service dont peuvent disposer les aînés et qui peut être utilisé par quiconque en fait la demande. Cet inventaire permettra de mieux connaître le nombre, le type et la nature des services existants et de déterminer si tous les services de santé et services sociaux disponibles en français sont répertoriés, soit dans l’Annuaire des services en français de la Société franco-manitobaine. Ceci est important, car une plus grande visibilité des services disponibles en français contribue grandement à leur utilisation par les aînés francophones et leurs aidants lorsque le besoin survient. De plus, l’inventaire permettra d’identifier le type et la nature des services manquants auxquels la population vieillissante pourrait avoir recours.

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 4 - Identification des ressources humaines bilingues et des pratiques actuelles en matière de ressources humaines - de Moissac, Danielle; Ba, Halimatou; Roch-Gagné, Margaux; Gagné, M. (Université de Saint-Boniface, 2012)
Le premier volet de l’étude globale « Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français », dressait un portrait des états de santé et des besoins de services des personnes ainées de ces deux quartiers. Le deuxième volet de l’étude portant sur l’identification des services de santé disponibles en français, a permis de répertorier 106 organismes des secteurs public, communautaire, privé à but lucratif et privé à but non lucratif offrant des services de santé en français à Saint-Boniface et à Saint-Vital. Les buts du présent volet sont 1) de repérer les ressources humaines bilingues pouvant servir les aînés en français au sein de ces mêmes organismes en prenant en considération tout le continuum de soins et 2) de mieux comprendre les pratiques actuelles et les défis entourant le recrutement, l’embauche et la rétention des professionnels pouvant offrir des services en français. Plus précisément, nous tenterons de déterminer le nombre et le pourcentage de professionnels pouvant offrir des services en français, d’identifier la nature des services offerts par ces professionnels bilingues, de définir les pratiques actuelles quant au recrutement et à l’embauche de personnel bilingue et de cerner les défis quant au jumelage des besoins des aînés avec les ressources humaines bilingues disponibles. Ainsi, nous disposerons d’un portrait des ressources humaines bilingues et des pratiques actuelles en matière de ressources humaines quant aux établissements désignés bilingues ou francophones, aux établissements de soins de longue durée et aux fournisseurs de soins à domicile à Saint-Boniface et à SaintVital.

Improving St. Boniface and St. Vital seniors' access to French-language health services. Objective 4 - Identification of current bilingual human ressources and human resource practices - de Moissac, Danielle; Ba, Halimatou; Roch-Gagné, Margaux; Gagné, M. (Université de Saint-Boniface, 2012)
The first part of the comprehensive study entitled “Improving St. Boniface and St. Vital Seniors’ Access to French-language Health Services,” provided an overview of the health status and service needs of seniors in these two neighborhoods. The second part, focused on identifying available French-language health services, listed 106 public, community, private forprofit and private not-for-profit and community organizations offering Frenchlanguage services in St. Boniface and St. Vital. The goals of this fourth part of the study are to: 1) identify bilingual human resources able to serve seniors in French within these organizations across the continuum of care and 2) better understand current practices and challenges in recruiting, hiring and retaining professionals who can offer French-language services. Specifically, we will attempt to determine the number and percentage of professionals who can offer French-language services, identify the nature of services offered by these bilingual professionals, identify current practices for recruiting and hiring bilingual staff and identify the challenges in matching the needs of seniors with bilingual human resources. This will provide us with an overview of current bilingual human resources and human resource practices in designated bilingual or Francophone facilities, long-term care facilities and home care providers in St. Boniface and St. Vital.
Voir le rapport en anglais à partir de la page 36 du PDF joint.

Agir ! Pour ma santé : une intervention harmonisant Services médicaux et diagnostiques et services communautaires pour les Franco-Manitobains souffrant de dépression - de Moissac, Danielle; Bohémier, Moniqu; Herdman, Chelsea; Roch-Gagné, Margaux; Paillé, Julie; Johnston, Christine; Arpin-Molinski, Michelle; Dupuis, Georgette; Saint-Hilaire, Mélanie; Prairie, Liliane (Reflets, 2012)

Défis associés à l’offre de services de santé et de services sociaux en français au Manitoba : perceptions des professionnels - de Moissac, Danielle; de Rocquigny, Janelle; Giasson, Florette; Tremblay, Cindy-Lynne; Aubin, Natalie; Charron, Marc; Allaire, Gratien (Reflets, 2012)
Les services de santé et les services sociaux en français ne sont accessibles qu’auprès d’un quart de la population francophone au Manitoba (de Moissac, 2011). Une pénurie de professionnels pouvant offrir des services en français est perçue comme un obstacle important pour les usagers qui recherchent ces services et pour les professionnels qui voudraient assurer un suivi en français pour leurs clients. Une hésitation à s’identifier comme francophone et un manque de connaissance des ressources disponibles en français contribuent-ils à cette perception de pénurie? Cet article traite des défis entourant l’offre de services de santé et de services sociaux en français au Manitoba et suggère des pistes de solutions. Mots-clés : disponibilité, accessibilité, minorité francophone, Manitoba, professionnels

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 1 – Portrait de la santé, de l’accès aux services et des besoins en santé des personnes âgées - De Moissac, Danielle; Roch-Gagné, Margaux (Conseil communauté en santé du Manitoba, 2012)
Les aînés francophones du Manitoba représentent une population particulièrement vulnérable en ce qui a trait à la santé et à l’accès aux services de santé dans leur langue maternelle. Des analyses secondaires de l’Enquête de santé dans les collectivités canadiennes suggèrent que de vivre en situation linguistique minoritaire peut influencer la santé (Bouchard et collab., 2009). Certains facteurs sociodémographiques associés aux francophones en situation minoritaire contribuent à des disparités de santé : un taux de vieillissement plus élevé, une sous-scolarisation, un plus faible revenu et un plus grand pourcentage vivant en région rurale (Bouchard et collab., 2009). On reconnait qu’au Manitoba, la population francophone vieillit plus rapidement que la population anglophone et semble être en moins bonne santé que les non francophones du même âge (Chartier et collab., 2012). La sous-scolarisation, l’unilinguisme francophone et l’usage prédominant de la langue maternelle lorsque la santé physique et émotionnelle est en péril contribuent également à un plus grand besoin d’accès des aînés aux services dans leur langue (Allaire et collab., 2010). L’accessibilité aux services de santé en français est limitée, avec seulement près de la moitié des francophones ayant accès à un médecin de famille pouvant offrir ses services en français (de Moissac et collab., 2011). La langue dans laquelle les services de soins de santé sont reçus étant particulièrement importante pour la population vieillissante, il va de soi que la planification des soins de santé en français au Manitoba doit prévoir un accès à des services de qualité et sécuritaires pour les aînés francophones du Manitoba. Cela explique pourquoi le Conseil communauté en santé du Manitoba a ciblé les aînés comme l’un des groupes prioritaires pour recevoir des services en français (CCS, 2009). Le but principal de cet objectif est donc de dresser un portrait de l’état de santé des personnes francophones du Manitoba âgées de 65 ans et plus résidant à Saint-Boniface et à Saint-Vital. Une description de l’état de santé des aînés vivant dans la communauté, des aînés ayant recours aux soins à domicile et des aînés vivant dans un foyer de soins de longue durée sera d’abord présentée. La disponibilité et l’accessibilité des services de santé et des services sociaux en français dans ces quartiers seront ensuite examinées. Enfin, les besoins des aînés en matière de services de santé, tant pour les personnes autonomes que pour les personnes en perte d’autonomie et dépendantes, seront cernés.

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 5 - Description des expériences de trajectoires individuelles de soins de santé en français pour les aînés | Improving St. Boniface and St. Vital seniors' access to French-language health services. Objective 5 - Description of experiences of seniors' individual trajectories in French-language health care - Éthier, Sophie; Ba, Halimatou; Belzile, Louise; Gagné, Maryanne; Roch-Gagné, Margaux (Conseil communauté en santé du Manitoba et Université de Saint-Boniface, 2012)

Le statut socioéconomique des anglophones du Québec : ceux qui sont partis et ceux qui sont restés - Floch, William; Pocock, Joanne (Déclin et enjeux des communautés de langue anglaise du Québec, 2012)

La prise en compte de la langue dans les foyers de soins pour personnes âgées - Forgues, Éric; Gaucher, Charles; Guignard Noël, Josée; Kabano, John; Michaud, Jacques (Institut canadien de recherche sur les minorités linguistiques, 2012)

Linguistic variables: A necessity for health services planning tailored to the needs of Francophones. Current Status - French Language Heatlh Services Network of Eastern Ontario (Current Status, 2012)
fs-ref-orig: French Language Heatlh Services Network of Eastern Ontario. (2012). Linguistic variables: A necessity for health services planning tailored to the needs of Francophones. Current Status. fs-code-orig: French Language Heatlh Services Network of Eastern Ontario-2012

Examining the geographic distribution of French-speaking physicians in Ontario - Gauthier Alain P.; Timony Patrick E.; Wenghofer, Elizabeth. F. (Canadian Family Physician, 2012)
Abstract: Objective: To determine how many physicians in Ontario express a proficiency in providing services in the French language, and to assess the geographic distribution of such physicians. Design: Population-based analysis of the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. Setting: Ontario. Participants: A total of 22688 GPs, FPs, and other specialists certified by the College of Family Physicians of Canada and the Royal College of Physicians and Surgeons of Canada who responded to the survey. Main outcome measures: First official language spoken and languages of competency to conduct practice. Results: The physician-to-patient ratio by first official language spoken is 1 physician per 138 Francophone patients in Ontario. There is 1 French-speaking GP or FP for every 297 Francophone patients, and most French-speaking physicians are located in southern Ontario (91.4%), at a ratio of 1 physician per 111 Francophone patients. The most promising French-speaking physician–to–Francophone patient ratios are found in southern Ontario (1:248 for GPs and FPs, and 1:202 for other specialists) and in urban Ontario (1:266 for GPs and FPs, and 1:209 for other specialists). Conclusion: Clearly, there is a promising number of physicians, relative to the amount of French-speaking residents in Ontario, who identified a competency in offering services in French. However, while the number of physicians who indicated a self-assessed competency to deliver health services in French is promising, it is the maldistribution of such services that is of concern. Thus, efforts must be made to attract French-speaking physicians to areas where there is the greatest demand, particularly in the northern part of the province. Résumé Objectif: Déterminer combien de médecins ontariens se disent compétents pour fournir, des services en français et vérifier la distribution géographique de ces médecins. Type d’étude: Analyse démographique du rapport de 2007 sur la réinscription annuelle à l’Ordre des médecins et chirurgiens de l’Ontario. Contexte: L’Ontario. Participants: Un total de 22 688 omnipraticiens (OP), MF et autres spécialistes diplômés du Collège des médecins de famille du Canada et du Collège royal des médecins et chirurgiens du Canada qui ont répondu à l’enquête. Principaux paramètres à l’étude: Première langue officielle parlée et langues de compétence pour la pratique. Résultats: En Ontario, le rapport médecin/patient dans le cas de la première langue officielle parlée est de 1 médecin pour 138 patients francophones. On compte un OP ou MF francophone pour 297 patients francophones et les médecins francophones sont localisés pour la plupart (91,4%) dans le sud de l’Ontario, où on observe 1 médecin pour 111 patients francophones. C’est dans le sud de l’Ontario que le rapport médecin francophone/patient francophone est le plus favorable (1/248 pour les OP et les MF, et 1/1202 pour les autres spécialistes) et dans les milieux urbains (1/266 pour les OP et les MF et 1/1209 pour les autres spécialistes). Conclusion: Il est certain qu’en Ontario, il y a un nombre encourageant de médecins qui, par rapport au nombre de résidents francophones, se sont dits compétents pour offrir des services en français. Malgré ce rapport favorable, c’est la mauvaise distribution de ces services qui est préoccupante. Il faudrait donc s’efforcer d’attirer des médecins francophones dans les régions où la demande est la plus forte, notamment dans le nord de la province.

Compétences linguistiques et qualité de services. Argumentaire pour des services de soins de santé en français de qualité - Gauthier, Hubert; Reid, Marc-André (Conseil communauté en santé en français du Manitoba, 2012)
Citation suggérée par les auteurs: GAUTHIER, Hubert et REID, Marc-André. Compétences linguistiques et qualité de services, Argumentaire pour des services de soins de santé en français de qualité, Rapport pour le compte du Conseil communauté en santé du Manitoba, déposé en mars 2012, 46 pages.

Linguistic Competence and Quality of Services - Business Case for Quality French-Language Health Care Services - Gauthier, Hubert; Reid, Marc-André (Conseil communauté en santé en français du Manitoba, 2012)
Citation suggérée par les auteurs: GAUTHIER, Hubert and REID, Marc-André. Linguistic Competence and Quality of Services, Business Case for Quality French-language Health Care, Report commissioned by Conseil communauté en santé du Manitoba, submitted in March 2012, 46 pages.

The language barrier : the overlooked challenge to equitable health care - Hussey, Nadia (South African Health Review, 2012)
This chapter examines the effects of language barriers on the access of patients and communities to quality health care. It also looks at communication challenges experienced by health professionals that provide this care. Using a case study of a rural hospital, the chapter highlights some of the challenges posed by the language barrier and explores current methods that English-speaking health professionals at this hospital use to overcome these difficulties. The case study findings indicate that the language barrier decreases work efficiency and the provision of holistic treatment. It makes communication time consuming, which increases frustration levels and decreases empathy, approachability and confidentiality. Current methods for overcoming problems include the use of untrained and ineffective interpreters - usually overworked nurses; linguistic codeswitching; and the use of a selection of key isiXhosa vocabulary. These methods have many drawbacks and are not suitable or sustainable. Recommendations for improving communication include the promotion of a culture of multilingualism, which includes language education as a part of professional development and the employment of trained interpreters. For multilingualism to occur, more research needs to be conducted, and the political will to address this problem must be demonstrated. Overcoming the language barrier needs to be prioritised and commitment must be made to implementing strategies that provide a multilingual patient base with a multilingual healthcare service.

Autonomie culturelle, cultures sociétales et vitalité des communautés de langue officielle en situation minoritaire au Canada - Landry, Rodrigue (Minorités linguistiques et société, 2012)
Partant d’un modèle macroscopique des facteurs associés à la vitalité d’une minorité linguistique en situation intergroupe, cet article présente cinq principes expliquant comment les structures sociales s’imposent sur les vécus langagiers des membres de la minorité. Ce même modèle montre comment tant les individus que la collectivité peuvent exercer leur autonomie langagière pour contrer ce déterminisme social. Le modèle de l’autonomie culturelle est explicité et appliqué aux communautés de langue officielle en situation minoritaire (CLOSM) dans le but de faire valoir leur besoin d’autonomie institutionnelle pour assurer leur vitalité au Canada. La reconnaissance du droit à l’autonomie culturelle pourrait être un mode de légitimation des droits propres à ces communautés. Les CLOSM sont décrites comme des prolongements des deux cultures sociétales qui constituent le fondement de la dualité linguistique canadienne. Mots-clés : autonomie culturelle, culture sociétale, vitalité linguistique, droits linguistiques, minorités linguistiques

Is Francophone language status associated with diffences in the health services use of rural Nova Scotians? - Langille, Donald; Rainham, Daniel; Kisely, Steve (Canadian Journal of Public Health, 2012)
L’étude a pour objet de vérifier empiriquement la validité d’un modèle théorique qui propose un système de relations liant la construction de l’identité ethnolinguistique à la satisfaction de vie, un aspect du mieux-être psychologique, et à l’autoévaluation de sa santé. Un échantillon de 8 124 élèves du secondaire, provenant de 30 conseils scolaires francophones situés à l’extérieur du Québec, a participé à l’étude. Les résultats sont conformes au modèle fondé sur la théorie de l’autodétermination, qui stipule que lorsque la construction identitaire se fait dans un contexte d’appui à des besoins psychologiques de base, elle est reliée au mieux-être psychologique de la personne. Abstract

Impact de la situation linguistique minoritaire sur les soins de santé pour les personnes âgées francophones de l’Ontario souffrant de maladies chroniques : partage des connaissances et rétroaction. Rapport de recherche - Lemonde, Manon; Boudreau, Françoise; Dufour, Suzanne (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)

Portrait des minorités de langue officielle au Canada : les francophones du Manitoba - Lepage, Jean-François; Bouchard-Coulombe, Camille; Chavez, Brigitte (Statistique Canada, 2012)
Réalisé grâce au soutien financier du Secrétariat des langues officielles de Patrimoine canadien, de Ressources Humaines et Développement des Compétences Canada (RHDCC) ainsi que du ministère de la Justice Canada, ce portrait de la population de langue française du Manitoba est le huitième d’une série de portraits démolinguistiques des minorités de langue officielle au Canada rédigés par la Section des statistiques linguistiques de Statistique Canada. Cette étude brosse un portrait statistique général de la minorité de langue officielle du Manitoba en s’appuyant sur des données de recensements de la population ainsi que sur celles de l’Enquête sur la vitalité des minorités de langue officielle au Canada menée en 2006. Le but d’un tel portrait est de présenter un ensemble de caractéristiques, de comportements et de perceptions de la population de langue officielle minoritaire en mettant en évidence les possibilités d’analyse que recèlent les données. Le présent document ne se veut ni un simple assemblage de tableaux ni une étude approfondie de la dynamique démolinguistique de la population de langue française au Manitoba. Il présente une information diversifiée sur un ensemble de thèmes et de problématiques qui revêtent un intérêt pour les minorités de langue officielle et pour quiconque s’intéresse à la situation passée, actuelle et future des populations de langue officielle en situation minoritaire au Canada. La première section de ce portrait démolinguistique porte sur le choix des critères de définition de la population de langue française au Manitoba qui seront utilisés aux fins de ce document ainsi que sur une brève description des sources de données utilisées. La seconde section présente différentes informations qui rendent compte de l’évolution de la population de langue française ainsi que sur la répartition et la concentration de cette population sur le territoire manitobain. Cette information est accompagnée d’une série de cartes géographiques présentée en annexe et d’un tableau détaillé sur l’effectif, le poids relatif et la répartition de la population de langue française au Manitoba. La troisième partie de ce portrait porte sur les principaux facteurs qui influent sur l’évolution de la population de langue française dans cette province ou qui en résultent, soit la fécondité, la transmission de la langue maternelle et l’effet de l’exogamie, la structure par âge, la mobilité linguistique intragénérationnelle, la migration interprovinciale et internationale. De plus, on y présente de l’information sur l’usage du français dans la sphère publique et sur l’évolution de la capacité de soutenir une conversation selon le groupe de langue maternelle. La quatrième partie porte sur quelques secteurs clés pour la vitalité des communautés de langue officielle en situation minoritaire tels qu’identifiés dans la Feuille de route pour la dualité linguistique canadienne 2008-2013 : agir pour l’avenir1, soit la santé, la justice, l’éducation et les médias, les arts et la culture. Nous y présentons également des statistiques sur la participation communautaire, les caractéristiques de l’emploi et du revenu ainsi que sur l’utilisation du français au travail. Finalement, la dernière partie de ce portrait présente des statistiques sur l’appartenance identitaire des francophones et leurs perceptions à l’égard de la présence du français dans leur communauté, de l’offre de services en français de la part du gouvernement fédéral, du respect des droits linguistiques ainsi qu’à l’égard du fait que des gens travaillent au développement de la communauté francophone.

Portrait of Official-Language Minorities in Canada: Francophones in Manitoba - Lepage, Jean-François; Bouchard-Coulombe, Camille; Chavez, Brigitte (Statistics Canada, 2012)
This demolinguistic portrait of the French-speaking population in Manitoba was undertaken with the financial support of Canadian Heritage’s Official Languages Secretariat, Human Resources and Skills Development Canada (HRSDC) and Justice Canada. It is the eighth in a series of demolinguistic portraits of official-language minorities in Canada, prepared by Statistics Canada’s Language Statistics Section. This study paints a general statistical portrait of the official-language minority in Manitoba based on data from the Census of Population and the Survey on the Vitality of Official-Language Minorities in Canada, conducted in 2006. The purpose of such a portrait is to present a set of characteristics, behaviours and perceptions of the official-language minority population, exploiting the analytical opportunities contained in the data. This document is intended to be neither a mere collection of tables nor an in-depth study of the demolinguistic dynamics of the French-speaking population in Manitoba. It presents a range of information on themes and issues that will interest official-language minorities and anyone concerned with the past, present and future situation of official-language minority populations in Canada. Section 1 of this demolinguistic portrait concerns the criteria used in this study to define the French-speaking population in Manitoba. It also provides a brief description of the data sources used. Section 2 presents varied information on the evolution of the French-speaking population and its geographic distribution and concentration in Manitoba. This information includes a series of appended maps and a detailed table on the size, relative weight and distribution of the French-speaking population in Manitoba. Section 3 concerns the main factors that affect or are affected by changes over time in this province’s French-speaking population: fertility; transmission of mother tongue and effect of exogamy; age structure; intragenerational linguistic mobility; and interprovincial and international migration. It also discusses the use of French in the public sphere and how the ability to conduct a conversation in that language has evolved according to mother-tongue group. Section 4 looks at a few sectors essential to the vitality of official-language minority communities, as identified in the Roadmap for Canada’s Linguistic Duality 2008–2013: Acting for the Future1: health; justice; education; and the media, arts and culture. It also provides statistics on community participation, employment and income characteristics, and the use of French at work. The last section of this portrait presents statistics on the identity of Francophones and their perceptions regarding the presence of French in their community, the provision of federal government services in French, the respect for linguistic rights, and the fact that people are working to develop the Francophone community.

Reference framework: Training for active offer of French-language health services - Lortie, L.ise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

Cadre de référence pour la formation à l’offre active des services de santé en français (n°978-0-9879240-1-8) - Lortie, Lise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

La situation socioéconomique des anglophones du Québec - Lussier, Marie-Hélène (Institut national de santé publique du Québec, 2012)
fs-ref-orig: Lussier, M.-H. (2012). La situation socioéconomique des anglophones du Québec. Institut national de santé publique du Québec. fs-code-orig: Lussier-2012a

The socioeconomics status of Anglophones in Québec - Lussier, Marie-Hélène (Institut national de santé publique du Québec, 2012)
fs-ref-orig: Lussier, M.-H. (2012). The socioeconomics status of Anglophones in Québec. Institut national de santé publique du Québec. fs-code-orig: Lussier-2012b

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, R., Brenda; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

Experiences of French speaking immigrants and non-immigrants accessing health care services in a large Canadian city - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda. R.; Musto, Richard; Quan, Hude; King-Shier, Kathryn. M. (International Journal of Environmental Research and Public Health, 2012)
French speakers residing in predominantly English-speaking communities have been linked to difficulties accessing health care. This study examined health care access experiences of immigrants and non-immigrants who self-identify as Francophone or French speakers in a mainly English speaking province of Canada. We used semi-structured interviews to gather opinions of recent users of physician and hospital services (N = 26). Language barriers and difficulties finding family doctors were experienced by both French speaking immigrants and non-immigrants alike. This was exacerbated by a general preference for health services in French and less interest in using language interpreters during a medical consultation. Some participants experienced emotional distress, were discontent with care received, often delayed seeking care due to language barriers. Recent immigrants identified lack of insurance coverage for drugs, transportation difficulties and limited knowledge of the healthcare system as major detractors to achieving health. This study provided the groundwork for future research on health issues of official language minorities in Canada. Keywords: immigrants; French language; health care access; family doctor; qualitative descriptive; official language minorities

Étude exploratoire : perceptions, croyances, connaissances et attitudes d’un groupe d’aînés francophones du Nouveau-Brunswick concernant la démence et son diagnostic - Pakzad, Sarah; Paulin, Marie-Claire; Jbilou, Jalila; Fontaine, Véronique; Bourque, Paul-Émile; Bélanger, Mathieu; Routhier, Nicholas; Lavoie, Anne Marise (Reflets, 2012)
Cette étude explore les perceptions, croyances, connaissances et attitudes d’un groupe d’aînés francophones du Nouveau-Brunswick face à la démence et à son diagnostic; le diagnostic précoce de la démence est crucial autant pour l’identification des causes réversibles que pour la mise en place rapide d’interventions de prévention secondaire. Quatre-vingt-onze francophones du Nouveau-Brunswick âgés de 65 ans et plus ont été interrogés face à la démence et à son diagnostic dans cette étude quantitative exploratoire. Entre autres, bien que les participants de cette étude aient rapporté avoir peur de recevoir un diagnostic de démence, la plupart voudraient recevoir le diagnostic s’ils en étaient atteints. Les résultats soulignent l’importance d’éduquer la population face à la démence et aux services d’évaluation de la démence. D’autres implications sont discutées. Mots-clés : Démence, diagnostic, intention, maladie d’Alzheimer, minorité linguistique

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

La variable linguistique en recherche. L'importance de la langue dans le processus de recherche [infographie] - Réseau de recherche appliquée sur la santé des francophones de l'Ontario (2012)

Les variables linguistiques : un impératif pour une planification de services de santé adaptée aux besoins des francophones. État des lieux - Réseau des services de santé en français de l’Est de l’Ontario (État des lieux, 2012)

Francophones living with HIV/AIDS in Ontario: The unknown reality of an invisible cultural minority - Samson, Andre. A.; Spector Noah. M. P. (AIDS Care, 2012)
A strong body of evidence demonstrates that education, prevention and intervention, in the context of HIV/AIDS, should take ethno-racial diversity into account. The current research focuses on the cultural sensitivity manifested by AIDS service organisation ASO professionals towards Francophone minority persons living with HIV/AIDS Francophone PHAs in the two main urban centres of Ontario: Ottawa and Toronto. More specifically, this qualitative research will describe two different points of view: Francophone PHA service users n17 and ASO professionals n12. Data were collected from multiple focus groups and analysed using a phenomenological methodology. The analysis revealed that an important difference exists in the perceptions of language as an integral part of ethno-racial diversity. For ASO professionals, language is perceived as a simple tool of communication. For Francophones living with HIV/AIDS, however, language is perceived as a way to convey sensitivity to their cultural reality and a full recognition of their Canadian citizenship. This research showed that cultural sensitivity should include a linguistic aspect when it comes to health-related services, especially in the context of an officially bilingual country.

Regards croisés Ontario-Québec : les services de soins de santé mentale des communautés de langue officielle en situation minoritaire de 1950 à nos jours - Thifault, Marie-Claude; Lebel, Marie; Perreault, Isabelle; Desmeules, Martin (Reflets, 2012)
Considérant qu’un Canadien sur neuf hospitalisé pour maladie mentale retournera à l’urgence moins d’un mois après sa sortie d’hôpital, il importe de documenter, dans une perspective socio-historique, les itinéraires « transinstitutionnels » des personnes souffrant de troubles psychiques. Nous proposons ici une note de recherche sur l’enquête que nous menons sur l’évolution des services de soins de santé mentale des communautés de langue officielle en situation minoritaire, en particulier, les communautés francophones de l’Est et du Nord ontarien ainsi que de la communauté anglophone de l’Ouest du Québec. Ces regards croisés entre deux régions francophones de l’Ontario et le Montréal anglophone visent une meilleure compréhension de l’impact des facteurs de « langue de service » et de « culture » sur la santé mentale des communautés francophones en situation minoritaire (CFSM). Mots-clés : services de santé mentale, désinstitutionnalisation, minorités linguistiques, Ontario, Québec

Étude sur les services de santé linguistiquement et culturellement adaptés : portrait pancanadien - Tremblay, Suzanne (Société Santé et Mieux-être en français du Nouveau-Brunswick, Société Santé en français et Santé Canada, 2012)

Study on linguistically and culturally adapted healths services: A pan-Canadian portrait - Tremblay, Suzanne (Société Santé et Mieux-être en français du Nouveau-Brunswick, Société Santé en français & Health Canada, 2012)

Assessment of validity for the “language spoken at home” variable in Québec death records: Summary. Language, determinant of health status and of services' quality - Trempe, Normand; Boivin, Marie-Claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)

La validité de la variable « Langue d’usage à la maison » du Fichier des décès du Québec : synthèse. La langue, déterminant de l'état de santé et de la qualité des services - Trempe, Normand; Boivin, marie-claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)

Comparing the rates of mental disorders among different linguistic groups in a representative Canadian population - Vasiliadis, Helen-Maria; Lepnurm, Marje; Tempier, Raymond; Kovess-Masfety, Viviane (Social psychiatry and psychiatric epidemiology, 2012)
Purpose We aimed to determine whether linguistic group influences reported prevalence rates for a number of common mental disorders. Methods Secondary data analyses of the Canadian Community Health Survey cycle 1.2 (CCHS 1.2) were carried out on representative bilingual French and English, monolingual French and English and other language groups in Canada. Past year prevalence of major depression, anxiety disorders (agoraphobia, social phobia, panic disorder) and alcohol abuse/dependence were ascertained using versions of the World Mental Health Composite International Diagnostic Interview (WMH-CIDI) questionnaire. Multivariate data analyses were used to model past year presence of a mental disorder as a function of linguistic group, defined as languages can converse in, and adjusting for socioeconomic, demographic and cultural factors. Results Overall, past year rates for the presence of a common mental disorder were 10.7% (9.7–11.7%) for the bilingual English; 9.0% (8.1–9.9%) for the bilingual French; 10.2% (9.8–10.6) for the monolingual English; 8.5% (7.7–9.3%) for the monolingual French; and 8.3% (6.1–10.4%) for the other language group. After adjusting for a number of socio-demographic, economic and cultural factors, the multivariate analyses showed that the linguistic groups were equally likely to report the presence of a past year common mental disorder. This was also true for comparisons between the bilingual participants responding in French and English. Conclusions The differences observed in the reported crude rates for the presence of mental disorders across the different linguistic groups in Canada were explained by socio-demographic, economic, and factors such as immigration, spoke a third language and province of residence, and not explained by language of interview.

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the increase in international mobility, healthcare systems should no longer be ignoring language barriers. In addition to the benefit of reducing long‐term costs, immigrant‐friendly organizations should be concerned with mitigating the way language barriers increase individuals’ social vulnerabilities and inequities in health care and health status. This paper reports the findings of a qualitative, exploratory study of the health literacy of 28 Francophone families living in a linguistic‐minority situation in Canada. Analysis of interviews revealed that participants’ social vulnerability, mainly due to their limited social and informational networks, influenced the construction of family health literacy. Disparities in access to healthcare services could be decreased by having health professionals’ work in alliance with Francophone community groups and by hiring bilingual health professionals. Linguistic isolation and lack of knowledge about local cultural organizations among Francophone immigrants were two important findings of this study.